3D printed polyurethane honeycombs for repeated tailored energy absorption. (15th December 2016) - Bates, Simon R.G.; Farrow, Ian R.; Trask, Richard S.
Abstract: Fused filament fabrication (FFF) 3D printing of thermoplastic polyurethanes (TPUs) offers a unique capability to manufacture tailorable, flexible cellular structures which can be designed and optimised for specific energy absorbing applications. This paper describes the first application of this methodology in the creation and experimental analysis of 3D printed cellular structures, which are capable of undergoing repeated compressions to densification without failure. A parametric study has been undertaken, capturing the energy absorbing capability of hexagonal arrays manufactured from two types of TPU, with relative densities 0.18–0.49. Arrays were subject to compressions at strain rates 0.03–0.3 s − 1 and were capable of absorbing energies over the range of 0.01–0.34 J/cm 3, before recovering elastically. Critically, samples attained a maximum energy absorbing 'efficiency' of 0.36, which is comparable to that of traditional expanded closed cell polyurethane foams. The energy absorption behaviour of all structures was found to be dependent on strain rate and cell orientation with respect to the compression direction. This study shows the clear potential of FFF 3D printing for the creation of a new breed of cellular architectures, which are not constrained by existing manufacturing principles, offering the designer the capability to create resilient architectures specifically tailored to operational applications and environmental conditions. Graphical abstract: Highlights: Thermoplastic polyurethane (TPU) honeycombs were designed and manufactured by fused filament fabrication 3D printing. The energy absorption capabilities of TPU honeycombs, with relative densities 0.18–0.49, were assessed. Compressive energy absorption behaviour of all structures was dependent on strain rate and cell orientation. Honeycomb structures absorbed energies over the range of 0.01–0.34 J/cm 3 up to densification, before recovering elastically. 3D printed samples attained a comparable energy absorbing efficiency to existing expanded closed cell polyurethane foams.